The Extent Of Health Practitioners' Knowledge (Attitudes, Practices) Regarding Adult Vaccination In Makkah, Saudi Arabia (The Review of Diabetic Studies, 2024)
Background: Adult vaccination plays a crucial role in preventing infectious diseases and reducing associated morbidity and mortality. However, there is limited research on the knowledge, attitudes, and practices of primary healthcare professionals regarding adult vaccination, particularly in the context of Makkah, Saudi Arabia.Objective: The study aimed to assess the level of knowledge, attitudes, and practices among primary healthcare professionals in Makkah regarding adult vaccination.Method: A cross-sectional study design was employed to assess the knowledge, attitudes, and practices of primary healthcare physicians, nurses, and health educators in Makkah, Saudi Arabia, regarding adult vaccination. Data was collected through self-administered questionnaires, which covered topics such as vaccine selection, vaccination schedules, contraindications, and attitudes towards adult vaccination. The collected data was analyzed using descriptive statistics and appropriate statistical tests to identify any significant differences among the healthcare professional groups.Results: The study surveyed 193 participants, predominantly female (61.1%) nurses (73.1%). The majority of participants displayed good knowledge and positive attitudes towards adult vaccination. Nurses were more likely to provide information, address concerns, and actively recommend adult vaccination.Conclusion: The study findings indicate that primary healthcare professionals in Makkah have a good understanding and positive attitudes towards adult vaccination, with nurses playing a significant role in promoting vaccination. These findings emphasize the importance of continuous education and support for healthcare professionals in promoting effective adult vaccination.